Management and Cost Accounting / Fifth Edition - Drury Colin (Thomson Learning, 2000)
The only text to cater to the needs of undergraduate, post-graduate, and professional students of Management Accounting. Introduction to Management and Cost Accounting, Cost Accumulation for Inventory Valuation and Profit Measurement, Information for Decision-Making, Information for Planning and Control and Performance Measurement, Cost Management and Strategic Management Accounting, The Application of Quantitative Methods to Management Accounting, Notes, Bibliography, Appendices, Index.